Dietary Protein Requirements of the New Zealand Black-Footed Abalone (Haliotis iris, Martyn 1784) - Tung, Che-Huang (Auckland University of Technology, 2010)
The aim of this thesis is to evaluate the nutritional aspects of dietary protein for the New Zealand black-footed abalone (Haliotis iris) as an aquaculture species, and thus provide an affordable option for formulated feeds to be used in this abalone industry. Young (4 hours) and mature (7 days) and nine of twenty strains were mixed to each other microalgal biofilms were tested for their effectiveness on H. iris larval early developmental processes (attachment, metamorphosis, settlement and survival). Amino acid profiles and percent biofilm cover of microalgae also were monitored. Significantly better effects on attachment, metamorphosis, settlement and survival were found when abalone were exposed to mature microalgal biofilms compared to young biofilms, but few significant differences were found among biofilms composed of different microalgal species. Attachment and metamorphosis did not appear to be affected by differences in essential or non-essential amino acid profiles in the diets, but positive correlations were found between developmental processes and total amino acid content and percent biofilm cover. Similar results were also found in dual strains experiment. Nine commercially available protein sources (white fish, red fish, blood, meat and bone, casein, soybean, gluten, maize protein, Spirulina) were used as sole protein sources in formulated diets, which was fed to juvenile H. iris at 18 °C for five months. Juvenile abalone fed with diets containing white fish, red fish, casein, soybean and Spirulina had significantly better growth than those of fed other protein sources, thus indicating that these diets could be suitable as sole protein sources for H. iris formulated feeds. Abalone juveniles fed soybean diets (with extremely low methionine content) had similar growth results as those fed fish meal diets, and did not show a decrease in certain amino acid content (such as methionine) in their soft body tissues. However, dietary amino acid profiles did affect the amino acid profiles of both soft bodies and shells, which may have caused changes in shell bio-mineralization. Red fish protein had the best performance and it was therefore used to determine protein requirements under two different temperature regimes (13-21°C and 8-16°C) that simulated the temperature regimes of the South and North Islands in New Zealand. Six different dietary protein levels (0, 10, 20, 30, 40, and 45%) made from red fish meal were fed to juvenile abalone for four months. Growth performance increased steadily with increasing dietary protein. A second-order polynomial curve fit showed differences in protein requirements between the two temperature regimes, which were 42-53% in low temperatures and 38-39% in high temperature regimes. Shell morphology of previous two dietary experiments shown that: dietary protein sources and levels strongly affected H. iris shell morphology. Significantly wider, higher and heavier shells were found in animals fed casein diets. Both fish meal diets resulted in abalone with flatter and heavier shells. High dietary protein levels also promoted the enhancement of shell width and shell weight, and high temperature environments produced heavier and thicker shells. In conclusion, dietary protein is an important factor for H. iris aquaculture. The content of dietary protein strongly affects settlement of larvae and growth of juveniles in H. iris. Dietary amino acid profiles can change amino acid profiles in both soft bodies and shells, which may cause changes in shell morphology. A dietary protein content above 40%, as can be provided with red fish meal in formulated diets, is recommended to improve H. iris production. Raising dietary protein contents can effectively recover the decreased growth that results from a low cultivation water temperature regime.
Keywords: Haliotis iris; Protein requirement; Temperature